Experimental confirmation of the leafhopper Cicadella cosmopolita as a potential vector of Xanthomonas vasicola pv. musacearum of enset in Ethiopia - Shara, Sabura; Garo, Gezahegn; Khamis, Fathiya M.; Kearsley, Elizabeth; Ocimati, Walter; Tefera, Tadele; Blomme, Guy (Springer Science+Business Media, 2025)
Abstract Enset Xanthomonas wilt (EXW), caused by Xanthomonas vasicola pv. musacearum ( Xvm ), severely impacts enset cultivation in the Ethiopian highlands. Enset is the main staple crop for around 20 million Ethiopians. While primarily spread through infected planting material and contaminated tools, farmers recently speculated that leafhoppers could potentially be an insect-vector for Xvm . This study provides the first experimental evidence that the leafhopper Cicadella cosmopolita (Signoret, 1853) acts as a vector for Xvm transmission between enset plants. Controlled net trials demonstrated that healthy enset plants developed EXW symptoms after exposure to leafhoppers that continuously fed on Xvm -inoculated plants. Putative Xvm cultures were isolated from symptomatic plants and leafhopper bodies (abdomen/thorax), from which their pathogenicity was confirmed through subsequent inoculations into healthy enset plants. DNA analysis verified the presence of Xvm in whole leafhopper samples, thorax/abdomen tissues, and cultures from symptomatic plants. Field surveys along two altitude bands ranging 1000‒3000 m above sea level (masl) revealed an increased leafhopper abundance at 1500‒2500 masl during the wet season, coinciding with higher EXW prevalence. Farmer interviews regarding leafhopper ecology, pest control and relation to EXW revealed limited overall knowledge and perceived impact. From the net trials, Xvm was detected in only 4 of 20 leafhopper samples, all from insects with continuous contact with infected plants, suggesting limited transmission potential under natural conditions. Given the omnipresence of the leafhoppers in several of the studied enset-production landscapes, best management remains the timely and complete removal of all diseased plants, the use of disease-free planting materials, and clean garden tools, which in turn will also keep the risk of secondary leafhopper-vectored transmission at a minimum. Extension services should emphasize the increased EXW transmission risk in areas with high leafhopper populations as part of an integrated EXW management strategy.